Geranylgeraniol potently induces caspase-3-like activity during apoptosis in human leukemia U937 cells - Masuda, Y.; Nakaya, M.; Nakajo, S.; Nakaya, K.
In a previous study, we showed that geranylgeraniol (GGO)is a potent inducer of apoptosis in human leukemia cells. The present study describes the effects of GGO on the activity of cysteine-dependent aspartate-directed proteases (caspases)in human leukemia U937 cells. The caspase-3 (CPP32)activity was increased in a time-dependent manner by treatment with 50 microM GGO, whereas no activation of caspase-1 (interleukin-1beta converting enzyme (ICE)) was observed in any time period under the same experimental conditions. Other isoprenyl compounds such as geraniol, geranylgerany-lacetone, and vitamin K2 had no measurable effects on the activities of either caspase-3 or caspase-1. A inhibitor that preferentially inhibits the caspase-3 related caspases, Z-DEVD-FMK, strongly blocked the GGO-induced DNA fragmentation. These results suggest the involvement of caspase-3 in GGO-induced apoptosis in U937 human leukemia cells.